PENGARUH GAYA HIDUP DAN MOTIVASI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MAJALAH MONITOR BANDUNG - Nandang Komara; Purwadhi Purwadhi; Rian Andriani (STIE Trisna Negara OKU Timur, 2022)
The role of the media is at the forefront of society's social control. Currently the mass media has a very important role in conveying a news to the public, as well as providing and presenting data and facts that occur all the time. The mass media itself is actually a means of conveying messages, people's aspirations, as a communication tool to spread news or messages to the public, either directly or indirectly, widely not separated from the Bandung Monitor Magazine. The purpose of this study was to determine how much influence lifestyle and consumer motivation on magazine purchasing decisions. In general, newspaper revenue sources are divided into two, namely from magazine sales and advertising sales. However, in general, the largest revenue comes from advertising sales. Newspaper companies must increase the level of advertising sales, because relying solely on circulation results will not be able to cover production costs and operating costs, let alone to obtain appropriate margins. The result of this research is that there is a positive and significant effect of lifestyle variables and consumer motivation on purchasing decisions either partially or simultaneously. Thus, the lifestyle and motivation of consumers are getting better, so the purchasing decisions of monitor magazines are also increasing.